PEMANFAATAN SUMBER DAYA KELAUTAN UNTUK PEMBERDAYAAN MASYARAKAT DI DESA BLANG MERANG KECAMATAN PANTAR BARAT KABUPATEN ALOR - Nurlaila B Arsyad; Umiyani Kona; Petrus Mau Tellu Dony (Adiba Aisha Amira, 2026)
This study aims to examine the utilization of marine resources as a means of community empowerment in Blang Merang Village, Pantar Barat District, Alor Regency. The research data analysis uses qualitative descriptive analysis. The data used in the study are qualitative data. Data collection techniques include field observation and interviews, interviews with figures such as Mr. Abdul Rasyid Mangkop. This study also focuses on being a medium to determine social relations between villagers in marine resource utilization activities, as well as providing education to the younger generation about the importance of maintaining local marine potential. Activities such as seaweed cultivation, fishing, mangrove fruit and lola collection, and processing of marine products become a forum for learning and community cooperation involving all village members. The utilization of marine resources is effective in providing a positive impact on community welfare and in instilling environmental conservation values.